PEMETAAN POTENSI DAN RENCANA BISNIS KOMODITI BERAS SULAWESI SELATAN (Mapping of Potencies and Business Plan Rice Commodity in South Sulawesi) - -, Muhammad Anshar (Teknosains, 2013)
otencies of rice commodity and arrange the business plan with Local Quatien (LQ) and feasibility analysis. Primer and secunder data were used. Location Quatient result show that agricultural sector in South Sulawesi especially on rice commodity were the basic sector/ the main priority, while feasibility analysis indicated, investment capital were needed for developing rice produc for trans island trading were Rp.1.380.500.000 with Rp. 185.237.000 of revenue each month and return on capital investment during 10 month. Expected, presenting the potencies and bussines plan document in order to develop the agribussines activities that could to attract the investors in carrying subsystems activities, upstream to downstream, so able to increase economics growth in South Sulawesi Province.Keywords: potency, bussines plan, agribusiness